2013
DOI: 10.1073/pnas.1306799110
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide 1 receptor induced suppression of food intake, and body weight is mediated by central IL-1 and IL-6

Abstract: Glucagon-like peptide 1 (GLP-1), produced in the intestine and the brain, can stimulate insulin secretion from the pancreas and alleviate type 2 diabetes. The cytokine interleukin-6 (IL-6) may enhance insulin secretion from β-cells by stimulating peripheral GLP-1 production. GLP-1 and its analogs also reduce food intake and body weight, clinically beneficial actions that are likely exerted at the level of the CNS, but otherwise are poorly understood. The cytokines IL-6 and interleukin 1β (IL-1β) may exert an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 57 publications
9
83
0
1
Order By: Relevance
“…Furthermore, an interaction between GLP-1 and IL-6 in the brain has been recently described, showing that activation of central GLP-1 receptors increases IL-6 expression in the hypothalamus and hindbrain. These data point towards a role of central IL-6 in mediating the anorexic and body weight loss effects of GLP-1 receptor activation [55].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 71%
“…Furthermore, an interaction between GLP-1 and IL-6 in the brain has been recently described, showing that activation of central GLP-1 receptors increases IL-6 expression in the hypothalamus and hindbrain. These data point towards a role of central IL-6 in mediating the anorexic and body weight loss effects of GLP-1 receptor activation [55].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 71%
“…The idea that GLP-1 acts via increased IL-6 at the CNS level (8,19) also gains support from a seminal report by Donath and colleagues (20) that GLP-1 is released from L cells in the gut in response to IL-6, and that this mediates metabolically beneficial effects of IL-6. Thus, IL-6 and GLP-1 seem to interact at several sites in the body, and these interactions, in general, appear to promote metabolic health.…”
mentioning
confidence: 97%
“…Recently published results indicate that IL-6 could be a central nervous system (CNS) mediator for the body weight-and food intake-reducing effects of another peripheral messenger of energy balance besides amylin: glucagon-like peptide 1 (GLP-1) (8). There are several similarities between GLP-1 and amylin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, acute icv-but not peripheral-injection of IL-6 in rats increased energy expenditure, suggesting that the antiobesity effects of IL-6 are exerted mainly through its actions on the CNS [83]. A recent study has shown that central injection of a GLP1 receptor agonist with well-known weight-lowering effects potently increased hypothalamic expression of IL-6 [85]. IL-6 can also be produced and released by skeletal muscle, and mediate the effects of exercise on metabolism [86].…”
Section: Hypothalamic Alterations In Obese Humansmentioning
confidence: 99%